The relationship between transformational leadership behaviors, leader-member exchange and organizational citizenship behavior - Asgari, Ali; Silong, Abu Daud; Ahmad, Aminah; Abu Samah, Bahaman (EuroJournals, 2008)
It has been proposed that issues of transformational and transactional leadership behavior should be incorporated in the study for predicting subordinate citizenship behaviors, as both the theories are based on transformational leadership behaviors. This research had two objectives: to assess the impact of six dimensions of transformational leadership behaviors – contribution and affect – on citizenship behavior and to test the mediating impact of the LMX on the transformational leadership behaviors citizenship relationship. The subjects of this study were all full-time employees with their managers who working in the educational organization in Iran. This study surveyed 220 respondents. The sampling frame of the respondents was obtained from educational organization in Shiraz city in Iran. Data were collected on a structured questionnaire containing standard scales of transformational leadership behaviors, LMX, and organizational citizenship behaviors. After establishing the psychometric properties of the scales, hypotheses were tested through statistical analysis of the data. Results indicate that dimensions of transformational leadership behaviors are more likely to predict citizenship behavior than the affect dimension of LMX. Further, LMX is not mediating the relationship of transformational leadership behaviors with citizenship behavior.